1986
DOI: 10.2135/cropsci1986.0011183x002600060030x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seeding Date, Plant Density, Moisture Availability, and Soil Nitrogen Fertility on Maize Kernel Breakage Susceptibility1

Abstract: The objectives of this study were to evaluate seeding date, plant density, moisture availability, and soil N fertility effects on maize (Zea mays L.) kernel breakage susceptibility. Three hybrids within each of three relative maturity (RM) groups (90, 100, 110 days by Minnesota Relative Maturity Rating System) were grown in separate seeding date and plant density studies at Arlington, WI [Plano silt loam (fine-silty, mixed, mesic, Typic Argiudoll)], in 1983 and 1984. Maize was seeded four times at 10-day inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
31
0
4

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 0 publications
5
31
0
4
Order By: Relevance
“…Maize with high irrigation level had the highest breakage susceptibility (Fig. 1B), which agreed with previous studies in maize (Bauer and Carter 1986;Kniep and Mason 1989). Kernel breakage susceptibility was based on the corneous-to-floury endosperm ratios.…”
Section: Effects On Physical Properties and Chemical Composition Of Msupporting
confidence: 91%
See 1 more Smart Citation
“…Maize with high irrigation level had the highest breakage susceptibility (Fig. 1B), which agreed with previous studies in maize (Bauer and Carter 1986;Kniep and Mason 1989). Kernel breakage susceptibility was based on the corneous-to-floury endosperm ratios.…”
Section: Effects On Physical Properties and Chemical Composition Of Msupporting
confidence: 91%
“…1D), which was in contrast with research on sorghum (Griess et al 2010). No relationship between kernel density and breakage susceptibility was found, which agreed with some previous studies (Bauer and Carter 1986;Kniep and Mason 1989). Crop rotation had a significant effect on maize test weight and true density (Fig.…”
Section: Effects On Physical Properties and Chemical Composition Of Msupporting
confidence: 86%
“…The influence of corn planting date on yield potential has been well documented in previous literature (Gupta, 1985;Bauer and Carter, 1986;Imholte and Carter, 1987;Nafziger, 1994;Swanson and Wilhelm, 1996;Lauer et al, 1999;Farnham, 2001;Nielsen et al, 2002;Bruns and Abbas, 2006;Van Roekel and Coulter, 2011). The methods used to summarize planting date findings and to derive recommendations vary within previous research, with findings generally beginning at a particular calendar day determined to be optimum and calculation of the yield loss as a percentage or as bushels per acre for each day of delay.…”
mentioning
confidence: 97%
“…Personal communications from livestock feeders and dry millers indicate that uniformity of kernel size is important, but has not been studied scientifically. Kernel weight has been shown to increase with increasing nitrogen application (Rendig and Broadbent, 1979;Cromwell et al, 1983;Bauer and Carter, 1986;Kniep and Mason, 1989).…”
mentioning
confidence: 99%
“…Physical quality is a primary concern of the corn dry milling industry to optimize the production of the highest value end-product of uniform, large flaking grits (Paulsen and Hill, 1985). Bauer and Carter (1986) and Kniep and Mason (1989) found that kernel breakage decreased and kernel density increased with nitrogen fertilizer application.…”
mentioning
confidence: 99%